HUBUNGAN INTERAKSI SOSIAL DENGAN KUALITAS HIDUP LANSIA DI UNIT PELAYANAN TERPADU (UPTD) GRIYA WERDHA KOTA SURABAYA TAHUN 2017 - Dina Andesty; Fariani Syahrul (The Indonesian Journal of Public Health, 2018)
The number of elderly in many countries is increasing, including in Indonesia. Along with the increasing number of elderly, many problems will be experienced by the elderly such as psychological disorders, pathological disorders on physical conditions, access to health services that is difficult to obtain and less social support from family or friends. Lack of social support will affect the social interaction of elderly. Social interaction can have a positive impact on the quality of life because the social interaction of the elderly do not feel lonely, therefore social interaction must be developed and maintained in the elderly group. The purpose of this study is to analyze the social interaction with the quality of life of the elderly in UPTD Griya werdha Surabaya. This study used cross sectional study design. The study population is all elderly in UPTD Griya Werdha Surabaya City. The sample size is as much as 52 elderly are taken using simple random sampling method. The dependent variable of the research is the quality of life of the elderly and the independent variable is social interaction. The research instrument used WHOQOL-OLD questionnaire. The result of the research shows taht there is relationship between social interaction with quality of life of elderly in UPTD Griya Werdha Surabaya ( p-value = 0.017). The conclusion of this study is social interaction related to the quality of life of the elderly, the worse the social interaction of the elderly, the lower the quality of life. The suggestion from this research is to increase social interaction of elderly by increasing daily activity of elderly in order to often gather and interact with each other.